2010
DOI: 10.1111/j.1540-8183.2009.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndromes in Treatment‐Naïve Black South Africans with Human Immunodeficiency Virus Infection

Abstract: Treatment-naïve HIV patients with ACS are younger and have fewer traditional risk factors than HIV-negative patients. HIV patients have less atherosclerotic but higher thrombotic burden which may imply a prothrombotic state in the pathogenesis of ACS in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 39 publications
(39 reference statements)
4
35
0
Order By: Relevance
“…These data are consistent with the high prevalence of smoking in HIV infected individuals with occlusive arterial disease in previous reports [3,18,25,26]. Smoking therefore represents an important confounder when assessing relationships between HIV and carotid IMT.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These data are consistent with the high prevalence of smoking in HIV infected individuals with occlusive arterial disease in previous reports [3,18,25,26]. Smoking therefore represents an important confounder when assessing relationships between HIV and carotid IMT.…”
Section: Discussionsupporting
confidence: 80%
“…The characteristics of the HIV positive patients with CLI in the present study were similar to those reported on in prior studies describing the presence of occlusive arterial disease in HIV infected African patients [17,18]. In this regard, as with these previous studies [17,18], HIV positive patients with occlusive arterial disease were younger and had considerably less conventional risk factors other than smoking than HIV negative patients.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…7,8 The presence of HIV/AIDS-associated comorbidity and co-infections have necessitated the concurrent use of SMX/TMP and antiretroviral medications containing LPV/r which have been shown to be of clinical benefits. 9 The concurrent use of LPV/r with SMX/TMP may possibly place more toxicological burden on the heart which pumps blood that serves as a means of drug transportation.…”
mentioning
confidence: 99%